Differential diagnosis of myelopathies - Sawaya, Raja; Nachef, Zahi (International Journal of Medicine, 2014)
We present a review on myelopathies. We introduce each category of etiologies by a case study, followed by a short review of the different causes of myelopathies in this category. We elaborate on clinical presentation, laboratory workup, imaging and treatment. This extensive review elaborates on myelopathies caused by demyelinating diseases, infectious agents, connective tissue diseases and vasculopathies, neoplasms, toxic substances, metabolic derangements and the idiopathic myelopathies. Interesting images are incorporated in this review. Keywords: myelopathies, spinal cord, demyelinating, infectious, neoplasm, idiopathic.